Electron Microscopic Observations on Actinophages for Streptomyces venezuelae - Painter, B. G. (1965)
Painter, B. G. (University of Minnesota, Minneapolis), and S. G. Bradley. Electron microscopic observations on actinophages for Streptomyces venezuelae. J. Bacteriol. 89:240–244. 1965.—Actinophages MSP2 and MSP8 were treated with various chemical agents to determine the phages' substructure. Normal MSP2 and MSP8, shadowed with uranium, or negatively stained with uranyl acetate or phosphotungstic acid, were tadpole-shaped. The average overall length of MSP2 was 245 mμ, and of MSP8, 206 mμ. The head width of both phages was approximately 58 mμ; the tail of MSP2 was 161 mμ long, and of MSP8, 137 mμ. Treatment of MSP2 and MSP8 with 7.5 m ammonium hydroxide at 56 C or 8 m urea at room temperature released some of the head contents, and revealed substructures in both the heads and the tails. The tails of phages treated with 7.5 m mercaptoethanol were destroyed.